KETENTUAN HUKUM TINDAK PIDANA PENCABULAN TERHADAP ANAK DIBAWAH UMUR MENURUT UNDANGUNDANG PERLINDUNGAN ANAK - Ony Rosifany (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2020)
One of the triggers for the crime of sexual immorality in this case is the rapid development of information and technology flows. Fornication is an act carried out by someone who is motivated by sexual desire to do things that can arouse lust, thereby causing self-satisfaction. What is troubling society is the criminal act of child sexual abuse, whether it is a boy or a girl. Fornication is an act committed by someone who is motivated by sexual desire.In general, the factors that cause the crime of child sexual immorality can be caused by internal factors as well as external factors.The legal provisions for the crime of child molestation against children are contained in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, stated in Article 76 E and Article 82.